Cooperative predation on mutualistic prey communities. (7th April 2020) - Banerjee, Swarnendu; Sha, Amar; Chattopadhyay, Joydev
Highlights: Predator cooperation can lead to extinction of the relatively more attacked prey. Minimal mutualism strength is required to maintain coexistence equilibrium. When cooperation is high, bistability between prey extinction and oscillatory coexistence increases survival chance of the otherwise extinct prey. Interaction between prey mutualism and predator cooperation can lead to equilibrium-cycle bistability and cycle-cycle bistability. The system demonstrates two different types of tristability. Abstract: Positive interactions are quite common in nature but are less studied. While positive association among species has been studied in ecological literature, how such interactions will impact the ecological dynamics when they occur within antagonist communities is not understood. Motivated by this, we studied a community module consisting of two prey species and a predator population where the prey species are in mutualistic relationship while the predators exhibit hunting cooperation. Our result reconfirms that both mutualism and hunting cooperation destabilizes the system. Predator cooperation may result in extinction of the relatively more attacked prey and a minimal mutualism strength is required in order to retain the coexistence equilibrium. A higher degree of cooperation among predators can lead to bistable dynamics which increases the survival chance of the otherwise extinct prey. Mutualistic association further enhances this effect thereby increasing the chance of coexistence. Generally, cooperative hunting is known to produce bistability but this system also demonstrated tristable dynamics. Moreover, the wide range of multi-stability exhibited by our model indicate the high sensitivity of the system to small perturbations. Overall, our study suggests that the interplay between the prey mutualism and predator cooperation may result in unintuitive dynamics which might be important in the context of community ecology.